Analysis of Stress State and Damage Characteristics of the Cement Sheath - Xu, Feng; Ren, Qingyang; Ling, Hao; Yin, Hongwu; Zhou, Xiaogui; Liu, Zhongshuai; Yang, Guangqing (Frontiers in Energy Research, 2022)
The sealing problem of the cement sheath often appears in gas wells for underground energy exploitation, especially when horizontal multistage fracturing technology is used in the shale gas industry. In this article, according to the elastic–plastic mechanics and Mohr–Coulomb yield criteria, an analytical solution of the equations is obtained by considering the effect of pressure on the fluid column, volume shrinkage, or expansion and geological characteristics on the initial stress of the cement sheath. The analysis of the example indicates that the smaller the initial stress of the cement sheath, the lower its radial stress and circumferential stress, which is under the maximum inner casing pressure of 150 MPa. With the increase of initial stress of the cement sheath, it is easier for the first and second interfaces to enter the plastic and damage state for the cement sheath. The smaller the initial stress of the cement sheath, the earlier the damage appears, and it develops with the increase of inner casing pressure more quickly. When the initial stress of the cement sheath is less than 7.9 MPa, the damage factor finally reaches 1 with the increase of internal casing pressure; however, when the initial stress of the cement sheath is greater than 34.2 MPa, the damage factor always remains 0 with the increase of inner casing pressure. The results preliminarily revealed that the initial stress of the cement sheath plays a decisive role in promoting its integrity and may provide guidance for the choice of the formula of cement and construction methods in the oil field.